Molecular Cloning and Characterization of cgs, the Brucella abortus Cyclic β(1-2) Glucan Synthetase Gene: Genetic Complementation of Rhizobium meliloti ndvB and Agrobacterium tumefaciens chvB Mutants - Iñón de Iannino, Nora (American Society for Microbiology, 1998)
The animal pathogen Brucella abortus contains a gene, cgs, that complemented a Rhizobium meliloti nodule development (ndvB) mutant and an Agrobacterium tumefaciens chromosomal virulence (chvB) mutant. The complemented strains recovered the synthesis of cyclic β(1-2) glucan, motility, virulence in A. tumefaciens, and nitrogen fixation in R. meliloti; all traits were strictly associated with the presence of an active cyclic β(1-2) glucan synthetase protein in the membranes. Nucleotide sequencing revealed the presence in B. abortus of an 8.49-kb open reading frame coding for a predicted membrane protein of 2,831 amino acids (316.2 kDa) and with 51% identity to R. meliloti NdvB. Four regions of the B. abortus protein spanning amino acids 520 to 800, 1025 to 1124, 1284 to 1526, and 2400 to 2660 displayed similarities of higher than 80% with R. meliloti NdvB. Tn3-HoHo1 mutagenesis showed that the C-terminal 825 amino acids of the Brucella protein, although highly conserved in Rhizobium, are not necessary for cyclic β(1-2) glucan synthesis. Confirmation of the identity of this protein as B. abortus cyclic β(1-2) glucan synthetase was done by the construction of a B. abortus Tn3-HoHo1 insertion mutant that does not form cyclic β(1-2) glucan and lacks the 316.2-kDa membrane protein. The recovery of this mutant from the spleens of inoculated mice was decreased by 3 orders of magnitude compared with that of the parental strain; this result suggests that cyclic β(1-2) glucan may be a virulence factor in Brucella infection.